2017
DOI: 10.1055/s-0043-123075
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Anti-inflammatory Effects of Equisetum arvense Are Not Solely Mediated by Silica

Abstract: , known as common horsetail, is used for the treatment of inflammatory diseases and is the plant with the highest concentration of silica. Yet it is unknown if the medicinal properties are mediated by its silica content. In the current study, optimal conditions for silica-rich horsetail preparations were identified. Bioactivity of the preparations was analyzed using flow cytometry-based activity and functionality profiling of primary human lymphocytes as well as cytokine measurement using a classical ELISA tec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…This relates to AM remedies, to understand their molecular, epigenetic, cellular, biochemical, physiological, pathophysiological, immunological, neurological, psycho-neuro-immunological mechanisms involved, the social context, etc. [43, 113, 114]. The same accounts to nonpharmacological interventions, lifestyle changes, or counseling: do they have effects on physiological rhythms, epigenetics, the psychosocial level, or on individual mental-cognitive developmental processes?…”
Section: Results: An Integrative Research Strategymentioning
confidence: 99%
“…This relates to AM remedies, to understand their molecular, epigenetic, cellular, biochemical, physiological, pathophysiological, immunological, neurological, psycho-neuro-immunological mechanisms involved, the social context, etc. [43, 113, 114]. The same accounts to nonpharmacological interventions, lifestyle changes, or counseling: do they have effects on physiological rhythms, epigenetics, the psychosocial level, or on individual mental-cognitive developmental processes?…”
Section: Results: An Integrative Research Strategymentioning
confidence: 99%
“…Briefly, the results of the present study demonstrated that the extract exhibits an antinociceptive effect in chemical models of nociception. In agreement with these results, Steinbor et al [85] verified the anti-inflammatory properties of E. arvense through its silica content, revealing that silica-rich horsetail preparations suppress lymphocytes' activation and proliferation by an interleukin-2-dependent mechanism and a downregulation of interferon gamma (IFN-c). Interestingly, analytical profiling by HPLC-UV-MS and bioactivity testing revealed significative immunosuppressive concentrations of a component that was identified as isoquercitrin.…”
Section: Other Properties Of Pharmacological Interestmentioning
confidence: 63%
“…The anti-cancer properties of Equisetum arvense are so well documented that a recent article published in 2020 states “[Equisetum arvense] may serve as an alternative anticancer agent for the treatment of pancreatic carcinoma with no or least side effects to the patient ” (73). Also the anti-inflammatory properties of the plant are well documented and the mechanism of action for the anti-inflammatory effect is based on modulation of interleukins and interferon (74). The rationale for using Equisetum arvense in the co-culture described above is based on two properties of the plant.…”
Section: Discussionmentioning
confidence: 99%